SARS-CoV-2 specific nanobodies neutralize different variants of concern and reduce virus load in the brain of h-ACE2 transgenic mice - Pavan, Florencia; Bok, Marina; Betanzos San Juan, Rafael; Malito, Juan Pablo; Marcoppido, Gisela Ariana; Franco, Diego Rafael; Militelo, Daniela Ayelen; Schammas, Juan Manuel; Bari, Sara Elizabeth; Stone, William B.; López, Krisangel; Porier, Danielle LaBrie; et al. (MDPI, 2024)
Since the beginning of the COVID-19 pandemic, there has been a significant need to develop antivirals and vaccines to combat the disease. In this work, we developed llama-derived nanobodies (Nbs) directed against the receptor binding domain (RBD) and other domains of the Spike (S) protein of SARS-CoV-2. Most of the Nbs with neutralizing properties were directed to RBD and were able to block S-2P/ACE2 interaction. Three neutralizing Nbs recognized the N-terminal domain (NTD) of the S-2P protein. Intranasal administration of Nbs induced protection ranging from 40% to 80% after challenge with the WA1/2020 strain in k18-hACE2 transgenic mice. Interestingly, protection was associated with a significant reduction in virus replication in nasal turbinates and a reduction in virus load in the brain. Employing pseudovirus neutralization assays, we identified Nbs with neutralizing capacity against the Alpha, Beta, Delta, and Omicron variants, including a Nb capable of neutralizing all variants tested. Furthermore, cocktails of different Nbs performed better than individual Nbs at neutralizing two Omicron variants (B.1.529 and BA.2). Altogether, the data suggest the potential of SARS-CoV-2 specific Nbs for intranasal treatment of COVID-19 encephalitis.